English - Kurnyshova, Yuliia (Journal of Regional Security, 2023)
Analogical reasoning is a discursive strategy often used by decision- and policy-makers, think tankers, academics, and cultural producers to either justify actions or learn lessons from references to events in the past. This comparative essay conceptualizes the drastic distinction between the functioning of analogical reasoning in Russian and Ukrainian discourses during the current war. The author argues that the asymmetry between the two modes of analogical reasoning is glaring when it comes not only to the interpretation of history, but also to the drastically dissimilar emotional modalities, understandings of ontological security and rationality, justice and many other concepts shaping Ukraine’s and Russia’s international agency.